Breaking down WAP's walls. - Wilhelm, Kathy (Far Eastern Economic Review, 2000)
Although the PC-accessed Internet is completely open, wireless Internet is currently limited. Some of the boundaries to a wireless Internet are the result of technical differences among telephone operators and handset manufacturers, and these impediments should be temporary. However, a bigger factor is the bitter competition among mobile phone operators for subscribers. Operators have formed partnerships with content providers in a race to develop mobile Internet services that will win loyalty from consumers, who have proved to be willing to switch from one provider to another. Some phone operators have demanded that Wireless Application Protocol (WAP) content providers sign exclusivity agreements. In addition, many seal their portals, which are menus of Internet services, from subscribers to rival services. Such special business tie-ups can make services very limited. According to analyst Frank Yu of Web Connection Research in Hong Kong, WAP is driven by a corporate mentality rather than being user driven. Tools being created by software firms to open WAP up are discussed.